Corporate characteristics and tax aggressiveness: Evidence from the mining sector in Indonesia - Ikhsan Irmi; Reni Oktavia; Sari Indah Oktanti Sembiring (Asian Journal of Economics and Business Management, 2022)
This article presents to find out the effect of corporation characteristics, such as though capital intensity, leverage, and firm size on tax aggressiveness. Based on the condition of tax revenues and the achievement of the tax ratio in assessing the performance of tax revenues, Indonesia has not been able to reach the target even since 2013. Many motivations drive companies to do tax aggressiveness either legally or illegally. Therefore, this article is necessary to find out the effect of capital intensity, leverage, and firm size on tax aggressiveness. This article uses quantitative data sourced from financial statements with research samples of non-oil and gas mining companies listed on IDX for the period from 2016 to 2020. Using panel data regression analysis, the results show that capital intensity, leverage, and firm size have no significant effect on the tax aggressiveness of non-oil and gas mining companies. It means that capital intensity, leverage, and firm size are not the right way for non-oil and gas mining companies to exercise tax aggressiveness. Further research is expected to use other factors as their CSR and GCG.